Comparative study among a Venezuelan clay, its modifications, and commercial clays - Choren, Eduardo; Moronta, Alexander; Huerta, Lenin; Meyer, Alfredo (Rev. Téc. Fac. Ing. Univ. Zulia)
A Venezuelan clay from Tinaquillo. Estado Cojedes and three modifications: a protonated fonn. obtained by changing metallic ions for protons. and two PILes, one of aluminum and another of trono were studied. The appiled characterization techniques were: X ray diffraction. chenúcal analysis, specific area measurement. IR spectrometry, thermal gravimetric analysis. differential thermal analysts, scanning electron núcroscopy. and zonal núcroprobe analysis. Likemse. the clays’ catalytic activity for the l -butene ollgomerization at room temperature was studied. gravime1:I1cally and spectroscopically. For compartson’s sake. the same techniques were applled to two cormercial activated clays. The clays studied present the general characteristics and behaviour of smectites. The results suggest that part of the structural hydroxyls participate in the reversible adsorption of olefins but do not either in their isomerization or in the oligomerization.